Eco‐evolutionary responses to recreational fishing under different harvest regulations. Issue 19 (11th September 2018) - Ayllón, Daniel; Railsback, Steven F.; Almodóvar, Ana; Nicola, Graciela G.; Vincenzi, Simone; Elvira, Benigno; Grimm, Volker
Abstract: Harvesting alters demography and life histories of exploited populations, and there is mounting evidence that rapid phenotypic changes at the individual level can occur when harvest is intensive. Therefore, recreational fishing is expected to induce both ecological and rapid evolutionary changes in fish populations and consequently requires rigorous management. However, little is known about the coupled demographic and evolutionary consequences of alternative harvest regulations in managed freshwater fisheries. We used a structurally realistic individual‐based model and implemented an eco‐genetic approach that accounts for microevolution, phenotypic plasticity, adaptive behavior, density‐dependent processes, and cryptic mortality sources (illegal harvest and hooking mortality after catch and release). We explored the consequences of a range of harvest regulations, involving different combinations of exploitation intensity and minimum and maximum‐length limits, on the eco‐evolutionary trajectories of a freshwater fish stock. Our 100‐year simulations of size‐selective harvest through recreational fishing produced negative demographic and structural changes in the simulated population, but also plastic and evolutionary responses that compensated for such changes and prevented population collapse even under intense fishing pressure and liberal harvest regulations. Fishing‐induced demographic and evolutionary changes were driven by the harvest regime, and the strength of responses increased with increasing exploitation intensity and decreasing restriction in length limits. Cryptic mortality strongly amplified the impacts of harvest and might be exerting a selective pressure that opposes that of size‐selective harvest. "Slot" limits on harvestable length had overall positive effects but lower than expected ability to buffer harvest impacts. Harvest regulations strongly shape the eco‐evolutionary dynamics of exploited fish stocks and thus should be considered in setting management policies. Our findings suggest that plastic and evolutionary responses buffer the demographic impacts of fishing, but intense fishing pressure and liberal harvest regulations may lead to an unstructured, juvenescent population that would put the sustainability of the stock at risk. Our study also indicates that high rates of cryptic mortality may make harvest regulations based on harvest slot limits ineffective. Abstract : We used an eco‐genetic individual‐based model that accounts for microevolution, phenotypic plasticity, adaptive behaviour, density‐dependent processes, and cryptic mortality sources to explore the consequences of a range of recreational fishing regulations, involving different combinations of exploitation intensity and minimum and maximum length limits, on the eco‐evolutionary trajectories of a freshwater fish stock. We observed fishing‐induced demographic and evolutionary changes that were driven by the harvest regime, and the strength of responses increased with increasing exploitation intensity and decreasing restriction in length limits. Cryptic mortality strongly amplified the impacts of harvest and might be exerting a selective pressure that opposes that of size‐selective harvest, decreasing the ability of harvest slot regulations to buffer harvest impacts.